2020
DOI: 10.26633/rpsp.2020.5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of national essential medicines lists in the Americas

Abstract: Objectives. To compare national essential medicines lists (NEMLs) from countries in the Region of the Americas and to identify potential opportunities for improving those lists. Methods. In June of 2017, NEMLs from 31 countries in the Americas were abstracted from documents included in a World Health Organization (WHO) repository. The lists from the Americas were compared to each other and to NEMLs from outside of the Americas, as well as with the WHO Model List of Essential Medicines, 20th edition (“WHO Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…PS has gained more prominence in the published literature over the years, covering a range of topics, including the development of the SUS 11,27 , health issues and health spending 28,29 , the evolution of pharmacoepidemiology 30,31 , and the discussion of activities and procedures designed to meet the population's health needs 32,33 . Despite the increasing presence of articles about PS in other national periodicals, journals in the field of public health like the C&SC remain focused more on the so-called "social" aspects of the pharmaceutical sciences.…”
Section: Discussionmentioning
confidence: 99%
“…PS has gained more prominence in the published literature over the years, covering a range of topics, including the development of the SUS 11,27 , health issues and health spending 28,29 , the evolution of pharmacoepidemiology 30,31 , and the discussion of activities and procedures designed to meet the population's health needs 32,33 . Despite the increasing presence of articles about PS in other national periodicals, journals in the field of public health like the C&SC remain focused more on the so-called "social" aspects of the pharmaceutical sciences.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Steiner et al. asserted that because of robust overlap between countries’ National Essential Medicines Lists (NEML) and those with a negotiated price through the Strategic Fund lists, the mechanism “may be influential in its intended goal of helping countries to improve access to some medicines” while helping to make medicines for both communicable and non-communicable diseases more affordable [10] .…”
Section: Improving Access To Medicines and Suppliesmentioning
confidence: 99%
“…Notably, the Strategic Fund has one of the most comprehensive lists of essential medicines and public health supplies offered in the Americas Region. In addition, Steiner et al.’s review found that the Strategic Fund's Medicines List included a greater variety of medicines than any of the NEMLs throughout LAC, and even recommended adapting NEMLs to the Strategic Fund list [10] .…”
Section: Improving Access To Medicines and Suppliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounding this is the emergence of multi-drug resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB) which incur higher treatment costs compared to drug-sensitive TB (DS-TB) [1] , [2] . Providing access to appropriate and essential TB medicines – medicines selected for their quality, safety, efficacy and cost-effectiveness [7] , [8] , [9] – should improve TB population health outcomes [1] , [10] .…”
Section: Introductionmentioning
confidence: 99%